ANALISIS BUTIR SOAL ULANGAN AKHIR SEMESTER GASAL BIOLOGI KELAS X DAN XI TAHUN PELAJARAN 2016/2017 DI SMAN 1 KAMPAK BERDASARKAN TEORI TES KLASIK - Sunarmi, Sunarmi; Prasetyo, Triastono Imam; Ramadhiana, Charinda Bella (Jurnal Pendidikan Biologi, 2016)
The research aims to know the result of qualitative and quantitative analysis of items, and improvement and conformity of the items with the indicators of Biology final test grade X and XI at SMAN 1 Kampak on 2016/2017 periode. The research method is descriptive with qualitative-quantitative approach. The results showed contents validity of the final test items in X and XI grade is 87,5% and 85,83%. Percentage of construct validity of the final test items in X and XI grade is 95,71% and 84,29%. Percentage of language validity of the final test items in X and XI grade is 89,16% and 91,67%. The percentage of difficult item in X grade is greater than the medium and easy item. The percentage of medium items in XI grade is greater than the difficult and easy items, but it does not reach 50%, so the proportion of final test in X and XI grade are not appropriate. The discriminating power of item in X and XI grade with very bad and bad criteria are more than or equal to 50%. The effectiveness of item distractor in X grade with very good and good criteria are 70%, while in XI grade are 20%. The reliability of final test in X grade is enough criteria, while in the XI grade is low criteria.